Synthesis of Sm doped SnO2 nanoparticles and their ethanol gas traces detection. Issue 18 (15th September 2021) - An, Dongmin; Liu, Nan; Li, Yan; Zhou, Qingjun; Wang, Qiong; Zou, Yunling; Lian, Xiaoxue
Abstract: Metal oxide semiconductor-based sensors are widely used in medicine, industry, agriculture and environmental protection. In this paper, a series of different molar ratios of Sm were doped into SnO2 nanoparticles through a coprecipitation route. The as-obtained Sm/SnO2 nanocomposites were analyzed by X-ray diffraction, X-ray photoelectron spectroscopy, field emission scanning electron microscopy, and transmission electron microscope. The results indicated that Sm doping reduced the size of SnO2 nanoparticles and an Sm-O-Sn bond formed on the surface of Sm/SnO2 nanocomposites. The gas-sensing examination of the Sm/SnO2 nanocomposite-based sensor was assessed, and the results displayed that the fabricated sensor with a 4% molar ratio of Sm-decorated SnO2 exhibited a high response (138.9) and outstanding selectivity towards ethanol gas at 160 °C, and the limit of detection was as low as 100 ppb, implying a potential application in trace gas detection. Finally, the enhancement response of the Sm-doped SnO2 nanocomposites was discussed.